2O Biomarkers of immune switch induced by a novel anti-macrophage antibody (anti-Clever-1 mAb; FP-1305) in MATINS trial patients with advanced solid tumours. (15th December 2019) - Hollmén, M; Virtakoivu, R; Jaakkola, P; Minchom, A; Jalkanen, S; Karvonen, M; Mandelin, J; Koivunen, J; Bono, P
Abstract: Background: A scavenger receptor CLEVER-1 is highly expressed on tumor associated macrophages (TAMs) and mediates the clearance of "unwanted" self-components. Pre-clinical studies demonstrate that CLEVER-1 inhibition increases TAM pro-inflammatory cytokine secretion and antigen presentation reactivating CD8+ T cell responses with robust anti-tumor activity (Viitala et al., 2019). Targeting CLEVER-1 could overcome the immunosuppressive tumor microenvironment and has led to the development of FP-1305, a humanized anti-CLEVER-1 IgG4-antibody. Methods: MATINS (Macrophage Antibody To INhibit immune Suppression) trial is a multicenter first-in-human phase I/II study (NCT03733990) to assess the tolerability, safety and preliminary efficacy of FP-1305 in patients with advanced, IO-refractory melanoma, cholangiocarcinoma, hepatocellular, colorectal, and pancreatic ductal adenocarcinoma. Biomarker analysis included CLEVER-1 determination, immune cell profiling by mass cytometry and analysis of cytokine production. Results: 11 patients (median age 57) were enrolled in four cohorts (0.3, 1.0, 3.0 or 10 mg/kg) and received 1-8 cycles (median 3) of FP-1305 every three weeks. FP-1305 has been well tolerated without dose-limiting toxicities and maximum tolerated dose (MTD) has not been reached. Promising early efficacy results have recently been reported (ESMO 2019, LBA19). FP-1305 dosing led to increased Th1 skewing (CXCR3 + CCR6 - ) of CD4 and CD8 T cell populations with downregulation of several inhibitory immune checkpoint molecules. Increase in circulating IFN gamma was detected but it was most prominent in the patient showing durable partial response. Conclusion: FP-1305 is the first macrophage checkpoint inhibitor candidate promoting immune switch with promising tolerability and clinical anti-tumor activity. FP-1305 represents a novel treatment option to provoke immune response against cold tumors. Clinical trial identification: NCT03733990. Legal entity responsible for the study: Faron Pharmaceuticals. Funding: Finnish Academy, Finnish Cancer Foundations, Sigrid Juselius Foundation, Faron Pharmaceuticals. Disclosure: M. Hollmén: Research grant / Funding (institution), Travel / Accommodation / Expenses, Shareholder / Stockholder / Stock options: Faron Pharmaceuticals. P. Jaakkola: Advisory / Consultancy: Faron Pharmaceuticals. A. Minchom: Advisory / Consultancy: Faron Pharmaceuticals. S. Jalkanen: Shareholder / Stockholder / Stock options: Faron Pharmaceuticals. M. Karvonen: Shareholder / Stockholder / Stock options, Full / Part-time employment: Faron Pharmaceuticals. J. Mandelin: Shareholder / Stockholder / Stock options, Full / Part-time employment: Faron Pharmaceuticals. J. Koivunen: Advisory / Consultancy: Faron Pharmaceuticals; Advisory / Consultancy: Novartis; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Boehringer-Ingelheim; Advisory / Consultancy: KaikuHealth. P. Bono: Advisory / Consultancy, Travel / Accommodation / Expenses, Spouse / Financial dependant: Faron Pharmaceuticals; Advisory / Consultancy, Travel / Accommodation / Expenses: MSD; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Novartis; Advisory / Consultancy: Bristol-Myers Squibb; Advisory / Consultancy: OrionPharma. All other authors have declared no conflicts of interest.